The Sharia Law of Ramadan Fasting for People with Autism Spectrum in the Perspective of Islam - Damanik, Jaya Perwira (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Fasting is refraining from all kinds of things that can break the fast, starting from dawn to sunset with the intention. In one year there is one month that is required to fast for Muslims, namely the month of Ramadan. The purpose of this research is to find out the law of fasting for people with autism spectrum in the perspective of Islam. this research uses observational research methods with library methods through the reference of fiqh books and related books. The results of this study indicate that the month of Ramadan is a very special month, filled with various kinds of worship that bring us closer to Allah. In Islam, all people have the same position, as well as people with autism spectrum. They also have the same right to associate and socialize with everyone. And also people who are noble before Allah are not because of their physique and appearance, but those who are pious to Allah SWT. In conclusion, people with autism spectrum still have obligations to Allah SWT according to their abilities.